Impacto econômico da rede de feiras agroecológicas na região metropoplitana de João Pessoa e cidades próximas - Moura, Ivane de Pontes (2022)
Human activities are playing an increasing role in the environment, causing profound changes to the natural landscape at a faster pace than usual. According to the 2017-2018 Agricultural Census from the Brazilian Institute of Geography and Statistics, family farming is highly related to Brazil's socioeconomic development. The growth, integration and growing demand of the food sector for products and services that provide health and well-being, raise some questions that need to be discussed about the dynamics of the sector, mainly organic foods, such as: production, consumption, benefits, legality of certification and identification of the market value of organic agriculture. Reshaping the local market, encouraging the purchase of ecological foods on shorter commercial routes and narrowing the distance between farmers and consumers are some of the challenges to creating an ecologically correct food consumption model. The Food and Agriculture Organization of the United Nations (FAO), together with other organizations, indicates the short circuit as an alternative to family farming to explore new trends in food consumption and marketing and reflect the experiences of different countries in fairs and local markets. Direct trade is based on recommendations that the public and private sectors can implement to improve income performance and local development. The positive impacts expected from the increase in short-channel initiatives include the economic benefits of farmers and the provision of healthy food to consumers, as well as the strengthening of social relations, the conservation of natural resources and the increase in territorial sustainability. Thus, the objective of this work was to present and expand the discussion on the short circuits of agroecological fairs. This work is based on the extraction of the most recent information in the aggregation and synthesis of knowledge on the topic of the agroecological and organic market. The research was carried out together with the Network of Agroecological Fairs in the metropolitan region of João Pessoa, thus, the Social Control Bodies registered in the Brazilian Organic Conformity Assessment System that make up the Network and served by the research were a) ECOVARZEA; b) ECOSUL and c) ECOCAP. Some of the indicators analyzed were: a) Value added (VA) in agricultural production; b) VA in commercialization/processing; c) Quantity of food produced; d) Number of species sold; e) Quantity of food sold; f) Total VA contribution from fairs in the metropolitan region. After collecting the price variables and quantity of food sold, Descriptive Statistics were carried out. Within the sample universe of 64 stallholders (n) per month, the data on economic values were verified as the average of the economic values obtained by the stallholders. The data were subjected to analysis of variance (p<0.05), with the means performed using the Tukey test, using the Sisvar program (version: 5.6). Therefore, agroecological fairs are promising strategies, generating